Reduced direction discrimination sensitivity in visual motion adaptation, and the role of perceptual learning. (August 2021) - Karjack, Sabrina; Erlikhman, Gennady; Liu, Zili
Abstract: We investigated visual direction discrimination under the influence of motion aftereffect (MAE). Participants in each experiment first adapted to a horizontally drifting grating before deciding whether a drifting test grating moved to the left or right. A psychometric function was obtained as a function of the velocity of the test. Interestingly, in addition to the horizontal shift of the psychometric function that typified the MAE, the slope of the psychometric function became shallower after adaptation, indicating decreased discrimination sensitivity. However, this decrease was only observed in psychophysically experienced participants. Motivated, but psychophysically inexperienced participants only showed this effect after weeks of perceptual learning. This shallowing effect transferred to the untrained adaptation direction (e.g., from leftward adaptation to rightward), although perceptual learning of improved discrimination could not transfer. When the test duration was lengthened to reduce task difficulty, less training was needed to produce the same effect. These results indicate that, post-adaptation and when steady measurements could be obtained, left-right motion direction discrimination sensitivity was reduced.